Pengembangan Instrumen Penilaian Kemampuan Literasi Sains‎ ‎pada Pembelajaran Biologi - Pratiwi, Sakina Amaliah; Syamsiah, Syamsiah; Bahri, Arsad (Universitas Negeri Makassar, 2022)
Abstract. This study aims to develop a scientific literacy-based assessment instrument describe characteristics of the scientific literacy-based test instrument in Biology learning especially ecosystem material and validity test a scientific literacy test instrument developed in Biology learning especially ecosystem material. This type of research is Research and Development (RnD). The methods used include questionnaires and documentation. The test instrument developed was in the form of a description test equipped with supporting information for questions covering three indicators of scientific literacy, namely suitability of questions with various indicators, including indicators explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting scientific data and evidence. The final product of the science literacy-based test in Biology learning produces 10 items which are at the cognitive level of C1 (Remembering) to C6 (Creating). The validation results show that the instruments developed based on four aspects of assessment, namely material aspects (93%), construction (94%), language (93%), and scientific literacy (92%) are in the valid category with an average of 93% very worthy criteria. Keywords: test instruments, science literacy, biology learning